Are instructions in video format always better than photographs when learning manual techniques? The case of learning how to do sutures. (August 2016) - Ganier, Franck; de Vries, Philine
Abstract: In faculties of medicine today, a growing number of medical procedures are taught in manual techniques workshops. These workshops leave the students only very little time to train. One solution to this problem would be to provide medical students with an opportunity to practice these skills by themselves thanks to online learning materials. In order to determine the instruction presentation medium best suited to complete this training, different formats were compared (video + audio, video + text, and photographs + text). Forty-eight students were required to do five sutures using one of these formats. Their performance was assessed by time measurements and measurements of the quality of the knots. For all of the time indicators, the results show that the videos were more effective than the photographs for the first trial. This trend was reversed for the following trials, where the performance levels recorded using the photographs were better than those using the videos. The quality of the knots, however, was systematically better with the photographs than with the videos for all of the trials. Highlights: Three instruction formats for learning a medical suture task were compared. The results showed a learning curve for time to perform and quality of sutures. In the first trial, videos resulted in shorter times to perform than photographs. In subsequent trials, photographs produced better times to perform than videos. Performance levels with regard to quality were found to be higher with photographs.